The photocatalytic activity of g-C3N4/Ta2O5 composite under visible light irradiation - Viet Nga, Nguyen Thi; Vien, Vo (Vietnam Journal of Chemistry, 2017)
The g-C3N4/Ta2O5 composites were synthesized by heating mixtures of urea and Ta2O5 at 500 oC. The as-prepared samples were denoted as CN-500/TaO-W, where W is weight ratio of urea/Ta2O5 and equals to 3, 4 and 5. The materials were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, and Ultraviolet-visible diffuse reﬂectance spectroscopy. The photocatalytic activity of CN-500/TaO-W samples was assessed by degradation of methylene blue in aqueous solution under visible light. Among them, CN-500/TaO-4 exhibited the best performance. An enhancement in photocatalytic activity of the composites is believed to be the presence of g-C3N4. Keywords. g-C3N4, Ta2O5, photocatalytic activity, methylene blue, g-C3N4/Ta2O5 composite.